다중 핀홀 안경에 의한 시력과 조절력 변화 효과에 대한 연구 - 김정복; 추병선 (대한시과학회지, 17(3), 2015)
목 적: 다중 핀홀 안경에 의한 나안시력 및 조절력 변화에 대한 연구를 수행하였다. 방 법: 안질환과 양안시 기능에 이상이 없는 남자 17명, 여자 15명으로 총 32명을 대상으로 연구를 진행하였다. 피검사자들의 등가구면 굴절력은 우안 –1.33±1.10D, 좌안 –1.51±0.78D이었다. 1일 1시간씩 다중 핀홀 안경을 착용하게 하고 착용 전, 착용 2주 후, 착용 1달 후의 나안 양안시력과 양안 조절력을 측정하였다. 결 과: 다중 핀홀 안경을 1일 1시간씩 꾸준히 착용 후 나안 상태에서의 결과를 보게 되면, 원거리 시력은 착용 전 LogMAR 0.29±0.27에서 착용 2주 후 0.21±0.21, 착용 1달 후 0.15±0.17으로 시력 상승의 효과를 보였다.(p<0.000) 조절력 검사에서는 착용 전과 착용 2주 후보다 착용 1달 후의 조절력이 11.39D에서 13.59D로 측정되어 증가된 결과를 나타내었다.(p<0.02). 하지만 다중 핀홀 안경을 착용하지 않은 그룹에서는 통계적 유의성을 보이지 않았다. 결 론: 다중 핀홀 안경의 착용은 시력 향상에 도움이 될 수 있지만, 안정피로 유발 등의 불편함을 유발할 수 있어 지속적인 관찰이 필요할 것으로 사료된다. Purpose: The aim of the study was to investigate the effect of multi pinhole glasses as a corrective device for uncorrected visual acuity and accommodation. Methods: Participants of 17 male and 15 female without any ocular complication volunteered. The mean of equivalent refractive error were -1.33±1.10D for right eye and -1.51±0.78D for left eye. All participants were instructed to wear multi pinhole glasses for an hour a day for a month. Visual acuity and amplitude of accommodation were measured initially, after 2 weeks and after a month of wearing multi pihhole glasses. Results: There were statistically difference between time of measurement for the group of wearing multi pinhole glasses. Visual acuity improved from 0.29±0.27 logMAR initially, 0.21±0.21 logMAR after 2 weeks later and 0.15±0.17 logMAR one month later. Accommodative amplitude also improved from 11.39D to 13.59D at one month of wearing multi pinhole glasses. However there was no differecen found for the group without pinhole glasses. Conclusions: Results indicated that visual functions may be varied by wearing multi pinhole glasses. The multi pinhole glasses may improve visual acuity and accommodative amplitude. However the result of this study may be limited due to relatively short period of study and small number of participants. Therefore it is recommenced that long term study with large number of participants is needed for better understanding. KCI Citation Count: 0